Preferred reporting items for systematic review and meta-analysis of diagnostic test accuracy studies (PRISMA-DTA): explanation, elaboration, and checklist. (14th August 2020) - Salameh, Jean-Paul; Bossuyt, Patrick M; McGrath, Trevor A; Thombs, Brett D; Hyde, Christopher J; Macaskill, Petra; Deeks, Jonathan J; Leeflang, Mariska; Korevaar, Daniël A; Whiting, Penny; Takwoingi, Yemisi; Reitsma, Johannes B; et al.
Abstract : Systematic reviews of diagnostic test accuracy (DTA) studies are fundamental to the decision making process in evidence based medicine. Although such studies are regarded as high level evidence, these reviews are not always reported completely and transparently. Suboptimal reporting of DTA systematic reviews compromises their validity and generalisability, and subsequently their value to key stakeholders. An extension of the PRISMA (preferred reporting items for systematic review and meta-analysis) statement was recently developed to improve the reporting quality of DTA systematic reviews. The PRISMA-DTA statement has 27 items, of which eight are unmodified from the original PRISMA statement. This article provides an explanation for the 19 new and modified items, along with their meaning and rationale. Examples of complete reporting are used for each item to illustrate best practices.